2016
DOI: 10.1111/tbj.12633
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Surface Disease in Breast Cancer Patients Using Aromatase Inhibitors

Abstract: Aromatase inhibitors (AIs) are widely used as adjuvant hormonal therapy in postmenopausal women with hormone receptor-positive breast cancer. The purpose of this study was to investigate the potential impact of AIs on the anterior segment of the eye and especially the ocular surface. Participants in our study were 41 hormone receptor-positive early stage breast cancer patients (80 eyes), treated with AIs, while 80 eyes of 40 age- and gender-matched healthy controls, not previously used AIs for any purpose, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Several clinical studies evidenced that hormonal therapy with aromatase inhibitors impacts ocular surface and Meibomian glands, resulting in a significant proportion of cases with dry eye disease, associated with meibomian disfunction. In 7 studies (21)(22)(23)(24)(25)(26)(27), the diagnosis of dry eye was based on ophthalmic examination, whereas in the study of Cuzick et al (28), on self-reporting of signs and symptoms (Table I).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical studies evidenced that hormonal therapy with aromatase inhibitors impacts ocular surface and Meibomian glands, resulting in a significant proportion of cases with dry eye disease, associated with meibomian disfunction. In 7 studies (21)(22)(23)(24)(25)(26)(27), the diagnosis of dry eye was based on ophthalmic examination, whereas in the study of Cuzick et al (28), on self-reporting of signs and symptoms (Table I).…”
Section: Resultsmentioning
confidence: 99%
“…An OSDI >12 was considered to indicate dry eye in all studies included in the review (21,24,28). Among subjective signs reported by patients, the most frequent were foreign body sensation, blurred vision, redness, and photophobia (23,25). The alteration of the lacrimal film was strongly related to deficiency in the lipid layer, due to decreased meibomian function and blepharitis.…”
Section: Resultsmentioning
confidence: 99%
“…Although estrogen receptors are more readily associated with reproductive organs, they are also known to be present in the cornea, lens, retina, meibomian glands, and the lacrimal glands [7][8][9][10][11]. Several studies have reported on adverse ocular effects of AIs [12][13][14]. Inglis et al [4] used the Ocular Surface Disease Index questionnaire and found a significantly higher rate of self-reported dry eye disease in patients taking AIs compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Gibson et al noted no significant difference in ocular surface symptoms in AI users compared to controls but did note worse meibomian gland expressibility and pain perception in AI users [13]. Others have also reported increased rates of anterior segment pathology including meibomian gland dysfunction [14], blepharitis, superficial punctate keratitis, conjunctival injection [6,14], and Sjögren's syndrome in AI users [15]. One isolated case report documented epithelial deposits associated with exemestane use [5].…”
Section: Discussionmentioning
confidence: 99%
“…The patient’s visual acuity remained unaffected despite the persisting corneal changes. Chatziralli et al investigated the correlation between AI use and ocular surface disease [ 17 ]. Slit-lamp examination revealed blepharitis and meibomian gland dysfunction in 75% of the AI users compared to 42.5% of the control group.…”
Section: Reviewmentioning
confidence: 99%